Heaven Opens : The Trinitarian Mysticism of Adrienne von Speyr - Sutton, Matthew Lewis (Book collections on Project MUSE., 2014)
Adrienne von Speyr was one of the most important mystical theologians of the last century. However, her work has been eclipsed in many ways by her personal connection to Hans Urs von Balthasar. Heaven Opens provides one of the first comprehensive accounts of von Speyr's theology. Matthew Lewis Sutton argues that the eternal, immanent relations of the Triune God ground the mystical theological vision of von Speyr. Here, von Speyr's work is for the first time given an independent hearing, expositing its content, features, and connections, and assessing its contribution to contemporary Catholic t.